Flow and Heat Transfer Characteristics of S-CO2 in a Vertically Rising Y-Tube - Xiaohong Hao; Su Du; Qiguo Yang; Sen Zhang; Qi Zhang (Energies, 2022)
The supercritical carbon dioxide Brayton cycle has gradually become a research focus, but we also see a deficiency in research related to the flow and heat transfer characteristics of S-CO2 boiler staves with high parameters. In this paper, the flow and heat transfer of supercritical carbon dioxide is investigated in a 1000 MW supercritical boiler cooled wall tube in the parameters of a pressure of 30.42 MPa, a mass flux of 1592~2207 kg/(m2·s), and a heat flux of 39.8~71.2 kw/m2; a three-dimensional model of supercritical CO2 fluid in the cooling wall tube is established with the RNG k-epsilon turbulence model. Numerical simulations are carried out according to the following boundary conditions: an adiabatic half side, a heated half side, and a Y-type three-way two-to-one. The effects of the mass flux, inlet temperature, and heat flux on the flow and heat transfer characteristics in the Y-tube are analyzed, which exerts great influence on the research of S-CO2 boiler stave thermodynamics.